2012
DOI: 10.7314/apjcp.2012.13.11.5405
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Reorganizes miRNA Expression in a Mouse Model of Liver Fibrosis

Abstract: Asian Pacific J Cancer Prev, 13 (11), [5405][5406][5407][5408] IntroductionLiver is the main organ involved in gluconeogenesis and in production and transportation of fatty acids and cholesterol in which its metabolic disease is prerequisited for cancer. Tissue fibrosis is a major cause of dysfunction in the hepatic systems (Glass et al., 2011). Hepatic fibrosis is influenced by several epigenetic factors that control the wound-healing response. Fibrosis is the excess deposition of extracellular matrix (ECM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The miRNA-200 family was reported to be an important one in liver fibrogenesis1920. A recent study showed that miRNA-200a silencing activated HSC through Keap1, while overexpression of miRNA-200a inhibited HSC proliferation8.…”
Section: Discussionmentioning
confidence: 99%
“…The miRNA-200 family was reported to be an important one in liver fibrogenesis1920. A recent study showed that miRNA-200a silencing activated HSC through Keap1, while overexpression of miRNA-200a inhibited HSC proliferation8.…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism of action of curcumin is by interacting with enzymes or genes implicated in liver cirrhosis. Hassan et al [37] proved effect of curcumin by modulating miRNA 199 and 200 that are the main miRNA associated to liver fibrosis. They showed that miRNA 199 and 200 were increased by the administration of CCl4.…”
Section: +mentioning
confidence: 99%
“…In these models, curcumin showed a major role as an inhibitor of HSC activation; it also seems to be able to reduce liver damage, as well as the a-SMA and procollagen expression in the liver, when administered in CCl 4 -induced liver fibrosis models for 4-8 weeks. The recognized mechanism of action in those models included curcumin's ability to target multiple sites, such as platelet-derived growth factor-b receptor (PDGF-bR) [37], matrix metalloproteinases (MMPs) [37,38], tissue growth factor b (TGFb) [39,40], peroxisome proliferator-activated receptors (PPARc) [41], toll-like receptors (TLRs) [42], apoptotic pathway [43,44], inflammatory cytokines [41,42,45,46] and microRNAs [47,48]. Recently, curcumin's capacity to increase cyclic adenosine monophosphate levels, which leads to an increase in the number of mitochondrial DNA duplicates, has been demonstrated [49].…”
Section: Inflammation and Fibrosismentioning
confidence: 99%